SNPs in axon guidance pathway genes and susceptibility for Parkinson’s disease in the Korean population - Kim, Jong-Min; Park, Sue K; Yang, Jae Jeong; Shin, Eun-Soon; Lee, Jee-Young; Yun, Ji Young; Kim, Ji Seon; Park, Sung Sup; Jeon, Beom S (Journal of human genetics, 2011)
Single-nucleotide polymorphisms (SNPs) in genes of the axon guidance pathway have been reported to be a possible susceptibility factor for Parkinson’s disease (PD). This study investigated whether the genetic variability in the axon guidance pathway is a susceptibility factor in PD patients in the Korean population. A total of 373 patients and 384 healthy subjects were included. A set of 22 SNPs was analyzed, and the risk of PD was evaluated using odds ratios in an unconditional and conditional logistic regression models of age- and gender-matched subsets. A multidimensionality reduction (MDR) analysis was performed to explore potential gene–gene interactions. SNPs in the DCC , CHP , RRAS2 and EPHB1 genes of the axon guidance pathway showed significant associations with PD. The DCC rs17468382 and EPHB1 rs2030737 SNPs may be associated with increased PD risk, and the CHP rs6492998 and RRAS2 rs2970332 SNPs may be associated with reduced PD risk. However, no significant interactions for PD risk were found in the MDR analysis and logistic regression analysis using SNP interaction terms. This study supports that only four of the selected 22 SNPs are regulating factors associated with PD in the Korean population. However, no interactions were found among the SNPs, suggesting that the effect for the pathway as a whole is not greater than that for single genes in the Korean population. Further investigations involving populations of various ethnicities and other genetic markers and models are warranted.